HUBUNGAN TINGKAT PENGETAHUAN KELUARGA DENGAN TINGKAT RESIKO GPPH DI TK MUSLIMAT NURUL ANWAR DESA TALANGAGUNG - Ika Mauditya Fitri; Wiwit Dwi Nurbadriah; Galuh Kumalasari (Jurnal Keperawatan Terapan, 2020)
Child health development education about GPPH is very important given to families. Therefore, with the existence of health education, the incidence of GPPH in children can be reduced through the role of families in early detection of their children. This study also aims to determine the relationship between the level of family knowledge and the level of GPPH in Muslimat Nurul Anwar Kindergarten, Talangagung Village, Kepanjen District. The design of this research is Non Experimental with Cross Sectional approach. The sampling technique uses purposive sampling with a total of 43 respondents. The results showed that of 43 respondents who had knowledge of 51.16 percent and had children who were at high risk of GPPH as many as 62.8 percent. The instrument used was a closed questionnaire with 49 questions. The statistical test uses the Spearman Rank Test which shows the magnitude of the correlation coefficient between the two variables namely 0.838 with a significance of 0.029, which means there is a significant relationship between the level of family knowledge with the level of GPPH. It can be concluded that if family knowledge about early detection of GPPH is good then the level of GPPH in children can be suppressed. So the respondent is expected to be able to apply the knowledge gained to detect their children's growth and development abnormalities, especially regarding GPPH. Keywords: GPPH, Early Detection, Knowledge, Family.